BS EN 3479. Aerospace series. Steel X5CrNiCu15 5 (1.4545). Consumable electrode remelted. Solution treated and precipitation treated. Plates. 6 mm < a ≤ 20 mm. 1 070 MPa ≤ Rm ≤ 1 220 MPa. (16th September 2021) - British Standards Institution,
No abstract available